Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# If the points $\left( {2,0} \right){\text{, }}\left( {0,1} \right),{\text{ }}\left( {4,5} \right),{\text{ }}$and $\left( {0,c} \right)$ are concyclic, then the value of c is A. $-1$B. $1$C. $\dfrac{{14}}{3}$ D. $- \dfrac{{14}}{3}$

Last updated date: 18th Jul 2024
Total views: 448.8k
Views today: 5.48k
Verified
448.8k+ views
Hint: In order to solve this equation, we have to find out the value of c by using a circle equation that passes through the point (2,0), (0,1), (4,5), (0,c).

Concyclic points – A set of points are said to be concyclic, if they lie on a common circle. All concyclic points are the same distance from the centre of the circle.

By using Circle equation we get , ${x^2} + {y^2} + 2gx + 2fy + c = 0$
All the points (2,0), (0,1), (4,5), (0,c) will lie on this circle
For point A (2,0) -
${\left( 2 \right)^2} + {\left( 0 \right)^2} + 2 \times g \times 2 + c = 0$
$4 + 4g + c = 0$ ….. (1)
For point B (0,1)
${\left( 1 \right)^2} + {\text{ 2f}} \times {\text{1 + }}c{\text{ = 0}}$
$2f{\text{ + c + 1 = 0}}$ ….. (2)
For point (4,5)
${\left( 4 \right)^2} + {\left( 5 \right)^2} + 2g \times 4 + 2f \times 5 + c = 0 \\ 41{\text{ }} + 8g{\text{ }} + 10f + c = 0{\text{ }}.....{\text{(3)}} \\$
By solving these equations we get,
From $(1)$
${\text{ }}4 + 4g + c = 0 \\ c = - 4 - 4g \\ {\text{ }} \\$
Put the value of c in equation $(3)$
${\text{ }}41 + 8g + 10f - 4 - 4g = 0 \\ \Rightarrow {\text{ 37 + 4g + 10f = 0 }}....{\text{ (4)}} \\$
Again, put the value of ‘c’ from equation $(1)$, in equation $(2)$, we get,
${\text{ }}1 + 2f + c = 0 \\ \Rightarrow 1 + 2f - 4 - 4g = 0 \\ \Rightarrow 2f - 4g - 3 = 0{\text{ }}.....{\text{(5) }} \\$
From equation, $(4)$ and $(5)$, we get,
$37 + 4g + 10f = 0 \\ \& {\text{ 2f - 4g - 3 = 0}} \\$
$\Rightarrow 4g + 10f = - 37{\text{ }}...{\text{(A)}} \\ \Rightarrow {\text{2}}f - 4g = 3{\text{ }}....{\text{ (B)}} \\$
From equation $(A)$, we get
$\Rightarrow 4g = - 37 - 10f \\ \Rightarrow g = \dfrac{{ - 37 - 10f}}{4} \\ \Rightarrow g = \dfrac{{ - 1}}{4}\left( {37 - 10f} \right){\text{ }} \to {\text{(C)}} \\$
Put the value of $g$ from equation $(C)$ in $(B)$, we get
${\text{ }}2f - 4\left( {\dfrac{{ - 1}}{4}\left( {37,10f} \right)} \right){\text{ = 3}} \\ \Rightarrow 2f + 37 + 10f = 3 \\ \Rightarrow 12f + 37 = 3 \\ \Rightarrow 12f = - 34 \\ \Rightarrow f = - \dfrac{{17}}{6} \\$
Put the value of $f$ in equation $(C)$, we get
$g = - \dfrac{1}{4}\left( {37 + 10f} \right)$
$\Rightarrow {\text{ g = - }}\dfrac{1}{4}\left( {37 + 10\left( { - \dfrac{{17}}{6}} \right)} \right) \\ \Rightarrow {\text{ g = - }}\dfrac{1}{4}\left( {37 - \dfrac{{170}}{6}} \right) \\ \Rightarrow {\text{ g = - }}\dfrac{1}{4}\left( {\dfrac{{222 - 170}}{6}} \right) \\ \Rightarrow {\text{ g = - }}\dfrac{1}{4}\left( {\dfrac{{52}}{6}} \right) \\$
$\Rightarrow {\text{ g = - }}\dfrac{{13}}{6}$
Put the value of $g$ in equation $(1)$
${\text{ }}4 + 4g + c = 0 \\ \Rightarrow 4 + 4\left( { - \dfrac{{13}}{6}} \right) + c = 0 \\ \Rightarrow 4 - \dfrac{{52}}{6}{\text{ + c = 0}} \\ \Rightarrow \dfrac{{24 - 52}}{6}{\text{ + c = 0}} \\$
$\Rightarrow - \dfrac{{28}}{6} + c = 0 \\ \Rightarrow c = \dfrac{{14}}{3} \\$
$\therefore$ The correct answer is option C.

Note: Whenever we face such types of questions, the key concept is that we have to write what is given to us, like we did. Then we will apply the circle equation to calculate concyclic points, after deriving all the equations and solving them, we find the value of c and thus we get our answer.